Od Isera do Turnera i dalej. Na styku teorii recepcji i krytyki kognitywnej - Hamilton, Craig; Schneider, Ralf (Wydawnictwo Naukowe UAM w Poznaniu, 2012)
In this essay, we review the work of Wolfgang Iser, the major proponent of reception theory, and Mark Turner, the major proponent of cognitive criticism. The two theoretical lines advocated by Iser and Turner focus on the cognitive processes involved with reading literary texts. Unfortunately, bibliographic blind spots in both lines lead to the assumption that there is little overlap between reception theory and cognitive criticism. We put this assumption to rest by comparing and contrasting works by Iser and Turner in detail, starting with Iser’s work in the mid-1970s and ending with Turner’s work in the late 1990s.
From Iser to Turner and beyond: reception theory meets cognitive criticism